Assessment of the impact of the kinetic effect of ion parallel heat conduction on DEMO-relevant SOL plasma using integrated SOL-divertor code SONIC. (1st April 2022) - Homma, Yuki
Abstract: In plasmas of lower collisionality, such as the scrape-off layer (SOL) of a fusion tokamak device, the parallel heat conductivity of ions becomes smaller than the classical Spitzer–Harm model due to a nonlocal kinetic effect. We have assessed, by simulation, the impact and role of the kinetic effect of ion heat conductivity (abbreviated as ion KE in this paper) on DEMO-relevant tokamak SOL plasma, using the Japanese demonstration tokamak reactor concept JA DEMO. A series of test simulations, where the ion KE is modeled by a widely used free-streaming energy (FSE)-limited model, has demonstrated: (a) the ion KE decreases the ion parallel heat flux density in JA DEMO SOL (at the baseline operation scenario) around the X-point and further upstream of the low-field side (LFS) area along the separatrix, where the parallel collisionality is smaller. Up to 40%–60% decrease is observed, compared to the case without (w/o) ion KE, among the test cases where the ion KE level is scanned over the possible range (i.e. parameter α i of the FSE-limited model is varied over 0.2 ⩽ α i ⩽ 2.0 ); (b) the ion KE leads to significant increase in the ion temperature T i (up to 600% increase) and significant decrease in the ion density n i (up to −80%) over wide area of the SOL upstream. Energy balance analysis has suggested that the ion KE affects the upstream n i and T i by the power of 0.4 and −0.4, respectively, of the flux limiting factor, as long as spatial changes in plasma parameters are moderate. The results of this study serve as a fundamental assessment of the ion KE for DEMO- relevant SOL plasma, clarifying the need for further sophistication of the model toward more quantitative prediction.